Effectiveness of Death Penalty Against Crime of Abuse of Narcotics Agents or Statutory RI Number 35 of 2009 Concerning Narcotics Law as Viewed From The Principles of Justice And Humanity - Yuke Sinayangsih; Umar Ma'ruf (Jurnal Daulat Hukum, 2018)
In the process of law enforcement, the public prosecutor in demanding and Judge deciding cases narcotic crime in particular is not arbitrary impose the death penalty. Death penalty if that is the legal facts in the examination in the court proceedings indicates decent offender sentenced to death, for example: consideration of the type categorized as narcotics or weight considerations of narcotics to be sold or distributed. Narcotics law enforcement has become a concern for legislators us and see the impact of drug abuse. No doubt the legislators also provides severe criminal purpose that is the death penalty in order to provide a deterrent effect for the offender dealers or drug dealers. Although the death penalty is still ongoing and has not been abolished in Indonesia, people differ in responding as the number of countries that abolished the death penalty. On the one hand, there are groups of people expressed support that the death penalty is still needed in Indonesia moreover legally still recognized. Meanwhile, on the other hand there are groups of people who want the death penalty abolished. They argue that the provisions which apply the death penalty in Indonesia is not in accordance with the basic principles of the fundamentals of this country, namely 1945.Keywords: Criminal Die; Abuse Of Narcotics; Principle Of Justice And Humanityity